(а) 40+у=65
у=65-40
у=25
(б) 90-у=37
у=90-37
у=53
(в) 139+у=159
у=159-139
у=20
1. Раскройте скобки:
а) 3(2а + в - 8с)
б) - 4 (-х +3у - 4 т)
2.У выражение:
а) 2(8,5 - х) - (7,8 - 5х)
б) 3(2х + 5) +2(3 – х) - 4
в) 7а – 4(2а – 3в) + (6в + а)(-3)
3. Найдите значение выражения -3(2а-3в) + 6(а – 2в) – 3а при а = -1, в = 5.
4. Вынесите общий множитель за скобки:
а) 8а - 8в;
б) 12ху + 18ах.
Пошаговое объяснение:
1. Раскройте скобки:
а) 3(2а + в - 8с)
б) - 4 (-х +3у - 4 т)
2.У выражение:
а) 2(8,5 - х) - (7,8 - 5х)
б) 3(2х + 5) +2(3 – х) - 4
в) 7а – 4(2а – 3в) + (6в + а)(-3)
3. Найдите значение выражения -3(2а-3в) + 6(а – 2в) – 3а при а = -1, в = 5.
4. Вынесите общий множитель за скобки:
а) 8а - 8в;
б) 12ху + 18ах.
1. Раскройте скобки:
а) 3(2а + в - 8с)
б) - 4 (-х +3у - 4 т)
2.У выражение:
а) 2(8,5 - х) - (7,8 - 5х)
б) 3(2х + 5) +2(3 – х) - 4
в) 7а – 4(2а – 3в) + (6в + а)(-3)
3. Найдите значение выражения -3(2а-3в) + 6(а – 2в) – 3а при а = -1, в = 5.
4. Вынесите общий множитель за скобки:
а) 8а - 8в;
б) 12ху + 18ах.
Пошаговое объяснение:1. Раскройте скобки:
а) 3(2а + в - 8с)
б) - 4 (-х +3у - 4 т)
2.У выражение:
а) 2(8,5 - х) - (7,8 - 5х)
б) 3(2х + 5) +2(3 – х) - 4
в) 7а – 4(2а – 3в) + (6в + а)(-3)
3. Найдите значение выражения -3(2а-3в) + 6(а – 2в) – 3а при а = -1, в = 5.
4. Вынесите общий множитель за скобки:
а) 8а - 8в;
б) 12ху + 18ах.
а) 125+у-85=65
125+у=65+85
125+у= 150
у=150-125
у= 25
б) 144 -у-54=37
144-у=37+54
144-у=91
у=144-91
у= 53
в) 52+у+87=159
52+у=159-87
52+у=72
у= 72-52
у= 20